What Are the Outcomes and Views of People with Mobility Limitations After Participating in a Community Circuit Group? - Stavric, Verna; Mudge, Suzie; Robinson, Louise; Mewa, Michala (Physiotherapy New Zealand, 2017)
Increasing services are addressing the needs of people living with long term conditions. The purpose of this observational study was to determine the impact of community circuit classes on balance and mobility of individuals with neurological conditions. Participants were recruited from people interested in or already taking part in circuit classes provided at a private rehabilitation clinic. Outcomes (4-stage balance test, 30 second chair stand test and timed up and go (TUG) were assessed before and after a block of circuit classes (at least six weekly sessions). Risk and fear of falling were measured using the Falls Risk Assessment Tool and the Falls Efficacy Scale respectively. Participants completed a self-report questionnaire to provide their views about the class. All 13 participants completed at least six classes. A difference was found in the TUG (p = 0.05) but not in other outcome measures. All participants highly rated the organisation, level of staff skill and amount of assistance provided at the classes, but there was less satisfaction on the challenge and frequency of classes. Participating in circuit classes for a short-term period appears to have a positive impact on mobility and is an enjoyable form of exercise for people with neurological conditions.
Keywords: 4203 Health Services and Systems; 42 Health Sciences; Neurological; 1103 Clinical Sciences; 4201 Allied health and rehabilitation science